IT Service Continuity – Achieving Embeddedness through Planning - Niemimaa Marko; Järveläinen Jonna (My University, 2022)
Business customers and regulations as well as different IT service management frameworks expect that IT services are continuously operating. A service interruption might have severe impact on customer relationships, business, sales or image of the company. Therefore, organisations spend enormous amounts of time in continuity and recovery planning for IT services, and several continuity planning methodologies have been introduced. However, the connection between continuity planning and continuity management is somewhat unclear, and embedding the continuity practices into organisations have not been discussed in detail in planning methodologies. This paper will focus on how IT service continuity planning embeds continuity by reviewing continuity planning methods. The continuity planning practices that influence achieving embedded ness are analysed from qualitative and quantitative data from large organisations operating in Finland. The findings suggest that a number of planning practices support the transition from planning to embedded ness, such as creating awareness, increasing commitment, integrating the continuity practices into organisational processes and learning from incidents.
Proceedings of 2013 International Conference on Availability, Reliability and Security